Real- Time Analysis And Simulation ofEfficient Public Transport Monitoring System - Masthan, M; Raeen, MdMosahid; NasimAkhtar Begg, Mirza NasimAkhtar Begg; Patil, Veeresh (International Journal of Computer Sciences and Engineering, 2025)
This project proposed a method for safety measures which are necessary while driving vehicles. Road safety rules can be useful up to some extent to get away from accidents. If any misbehaviour occurs in vehicle due to driver, then a message will go to nearest police station along with the problem specification. That particular message includes the location of the bus where it is occurred. Our system can also detect alcoholic person who has been entering into bus. The alcoholic person may be driver or may be passenger. In our Project MEMS sensor is used to identify whether an accident takes place or not. If an accident takes place, a message will go to nearestpolice station.This project focuses on the implementation of a Real-Time bus Tracking System (RTBTS), by installing GPS (Global Positioning System)-module devices on buses which will transmit the current location on the GPS Receiver.We are using RFID based authentication for both passengersand driver. Fire sensor is used to monitor the fire in the bus if fire occurs in the bus send intimation to the owner and fire station. If this misconception occurs, then that message will go to nearest police station. In this way, we are indirectly providing safety to passengers and bus.